Determinants of Patient Loyalty in Inpatient Care Services in Mothers and Children's Hospital - Kanya Hapsari; Ayun Sriatmi; Apoina Kartini (Jurnal Penelitian Pendidikan IPA, 2023)
The decrease in the number of patient visits indicates low satisfaction and loyalty. RSIA BUNDA Semarang has experienced a decline in inpatient visits in recent years. The research objective is to analyze the influence of customer value, relationship marketing, and customer experience on their satisfaction and loyalty. This is quantitative research with a cross-sectional approach. Data were collected by interviews using questionnaires with 244 respondents. Data analysis uses the Structural Equation Modeling (SEM) test to test the influence between variables. The research results show that patient loyalty is not influenced by satisfaction, but is directly influenced by relationship marketing and customer experience variables, while satisfaction is influenced by customer value and customer experience. Patient satisfaction is not proven to be a mediator between customer value, relationship marketing, and customer experience in influencing patient loyalty. Mapping patient characteristics is an important step in understanding patient needs so that they can provide a positive experience for the services they receive, including building good customer relationships to create perceptions of positive value and trust